A Pair of Bacterial Siderophores Releases and Traps an Intercellular Signal Molecule: An Unusual Case of Natural Nitrone Bioconjugation. Issue 1 (4th December 2018) - Trottmann, Felix; Franke, Jakob; Ishida, Keishi; García‐Altares, María; Hertweck, Christian
Abstract: In microbial interactions bacteria employ diverse molecules with specific functions, such as sensing the environment, communication with other microbes or hosts, and conferring virulence. Insights into the molecular basis of bacterial communication are thus of high relevance for ecology and medicine. Targeted gene activation and in vitro studies revealed that the cell‐to‐cell signaling molecule and disease mediator IQS (aeruginaldehyde) of the human pathogen Pseudomonas aeruginosa and related bacteria derives from the siderophore pyochelin. Addition of IQS to bacterial cultures (Burkholderia thailandensis) showed that the signaling molecule is captured by a congener of another siderophore family, malleobactin, to form a nitrone conjugate (malleonitrone) that is active against the IQS‐producer. This study uncovers complex communication processes with derailed siderophore functions, a novel nitrone bioconjugation, and a new type of antibiotic against Gram‐negative bacteria. Abstract : Repurposing iron transporters : The siderophore pyochelin was found to be the true biosynthetic origin of IQS, a signaling molecule and virulence mediator of pathogenic bacteria such as Pseudomonas aeruginosa . In microbial interaction IQS is captured by another siderophore congener, malleobactin from Burkholderia thailandensis, to form an unusual nitrone conjugate that is active against the IQS producer.